مفهوم الحرية في الخطاب القرآني: دراسة موضوعية - Elatrash, Radwan Jamal Yousef (Islamic Reasearch Institute, 2012)
This article aims at discussing the concept of freedom from Qur’anic perspective; it examines its definition, forms of its availability, its association with choice, and moral guidelines for it. Among the important findings of this study, is that liberty according to the Qur’an, is the heaviest of human responsibility, rather than a privilege. Hence there is no compulsion in religion. the writer notes the absence of a word equivalent for proximate to the current meaning of freedom. He however, concludes that despite this fact the concept of freedom and liberty is integral to and inbuilt in the very core of the Quranic message. the writer concludes that the real kind of freedom and liberty is that which is voluntarily devoted to the obedience of God and not one which is pursued for its own sake without any purposeful direction.